2023
DOI: 10.3390/jmmp7040123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gas Metal Arc Welding Parameters on Bead Geometry and Material Distortion of AISI 316L

Samir Khrais,
Hadeel Al Hmoud,
Ahmad Abdel Al
et al.

Abstract: This study investigates the impact of gas metal arc welding (GMAW) parameters on the bead geometry and material distortion of AISI 316L. Three parameters—arc current in ampere (A), filler feed rate (m/min), and gas composition—were modified at varying levels in order to examine their effects. This study sheds new light on MAG welding lines’ physical properties and behavior and highlights the influence of quaternary shielding gas compositions. Taguchi analysis, which includes signal-to-noise (S/N) ratio and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The S/N ratio rank determined the most desirable welding parameters for producing the best AISI 316L/ER316L toughness have been determined as the arc current (160A), filler feed rate (4 m min −1 ), and gas mixture (G1), as determined by figures 15(a)-(d) and table 11 which display the appropriate values for each shielding gas content, arc current, and wire feed rate, it is evident that larger values are preferred. As reported in the study by Khrais et al [23]. ANOVA analysis demonstrated that the Gas combination has the most effect among the three parameters (arc current, filler feed rate, and gas mixture) and has the greatest impact on HAZ, with a contribution of 42.57%.…”
Section: Charpy Impact Testmentioning
confidence: 55%
See 4 more Smart Citations
“…The S/N ratio rank determined the most desirable welding parameters for producing the best AISI 316L/ER316L toughness have been determined as the arc current (160A), filler feed rate (4 m min −1 ), and gas mixture (G1), as determined by figures 15(a)-(d) and table 11 which display the appropriate values for each shielding gas content, arc current, and wire feed rate, it is evident that larger values are preferred. As reported in the study by Khrais et al [23]. ANOVA analysis demonstrated that the Gas combination has the most effect among the three parameters (arc current, filler feed rate, and gas mixture) and has the greatest impact on HAZ, with a contribution of 42.57%.…”
Section: Charpy Impact Testmentioning
confidence: 55%
“…To preserve the gas mixture's precision to two decimal points, it is crucial to employ the regulator valve to maintain a constant gas pressure and flow while welding. The recommended operating ranges for this purpose are between 0.021 to 0.05 MPa and 14 to 18 l min −1 , respectively [23].…”
Section: Shielding Gas Compositionmentioning
confidence: 99%
See 3 more Smart Citations